Design of Web-Based Mine Production Target and Realization Monitoring Information System with Waterfall Method - Hidayat, Dwi Nur; Chotijah, Umi (Cattleya Darmaya Fortuna, 2025)
Mining is a strategic industry in economic development, but it is usually based on production activity management bottlenecks, namely target monitoring and realization, which are mostly done manually. This includes recording errors, reporting delays, and difficulties in data analysis. The purpose of this research is to evaluate and develop a web-based target information monitoring system and production realization system at PT Gukusu using the Waterfall method. The Waterfall method is based on clearly defined system requirements from the beginning, allowing systematic system development from requirements analysis, system design (using UML), implementation (using PHP and MySQL), black-box testing, and testing to failure. It is expected that this system will improve work efficiency, data accuracy, and management's ability to thoroughly evaluate products Academically, this research contributes to system development.